(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2019)
Concern about teaching problem solving and mathematical thinkinghas paved way for the development of a writing-to-learn approach in math.This study explored whether journal writing can help the students in solving worded problems. Using the qualitative method of research, the students were required to make journals of their experiences in performing problem solving tasks. The students were required to do a lot of writing in their problem-solving activities. In making the journals, the students focused on key words, relationships, processes and lessons learned through writing statements, procedures and self-assessment. The students’ experiences as stated in their journal and transcripts of the interview served as the data in the study. Findings showed that students’ dispositions towards solving worded problems were altered with the use of writing and portfolio as their output. Journal writing as an approach in solving worded problems helped the students become more conscious about the way they conceptualize a problem for it to be solvable. It guided problem solvers in every step of their solutions. It also developed their communication skills and boosted their confidence to solve a math problem. The use of journal writing in solving worded math problems is highly recommended because it is essential for independent learning, improving communication skills, an approach for self–assessment, and interactive activity.